Hispania in Late Antiquity
1 online resource.
Keywords: Hispania in Late Antiquity: Current Approaches makes recent work on late antique Hispania available to a non-specialist audience outside the Iberian peninsula. The central theme of the volume is the integration of Hispania into the larger world of the later Roman empire. The contributors - archaeologists, historians, and historians of art - treat both the historical evidence and the historiographical context that has conditioned interpretation of that evidence. Topics covered include Christianization, urbanism, villas and land tenure, trade, and military topography. Taken together, the essays in this volume present a coherent and up-to-date picture of how Spain's late antique culture came into being, and how it was transformed in the course of the late antique centuries. Contributors: Javier Arce; Kim Bowes; Pedro Castillo Maldonado; Alexandra Chavarría; Pablo C. Díaz; M. Victoria Escribano Paño; Carmen Fernández-Ochoa; Michael Kulikowski; Fernando López-Sánchez; Neil McLynn; Luís R. Menéndez-Bueyes; Ángel Morillo Cerdán; Paul Reynolds.